2002
DOI: 10.1074/jbc.m109654200
|View full text |Cite
|
Sign up to set email alerts
|

Hyposmotic Stress Induces Cell Growth Arrest via Proteasome Activation and Cyclin/Cyclin-dependent Kinase Degradation

Abstract: Ordered cell cycle progression requires the expression and activation of several cyclins and cyclin-dependent kinases (Cdks). Hyperosmotic stress causes growth arrest possibly via proteasome-mediated degradation of cyclin D1. We studied the effect of hyposmotic conditions on three colonic (Caco2, HRT18, HT29) and two pancreatic (AsPC-1 and PaCa-2) cell lines. Hyposmosis caused reversible cell growth arrest of the five cell lines in a cell cycle-independent fashion, although some cell lines accumulated at the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…73,74 Moreover, CQ up to 100 M has no effect on cyclin or Cdk expression levels. 75 We did not find any significant cytotoxic effects or changes in levels of Cdk2 or cyclin E induced by CQ at the concentration used. The major effect of CQ is due to the increase in Ab-mediated internalization of HER2 and does not represent a synergism between 2 signaling pathways induced by CQ and HCT, respectively.…”
Section: Discussionmentioning
confidence: 84%
“…73,74 Moreover, CQ up to 100 M has no effect on cyclin or Cdk expression levels. 75 We did not find any significant cytotoxic effects or changes in levels of Cdk2 or cyclin E induced by CQ at the concentration used. The major effect of CQ is due to the increase in Ab-mediated internalization of HER2 and does not represent a synergism between 2 signaling pathways induced by CQ and HCT, respectively.…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, it has been reported that cyclic AMP inhibits translation of cyclin D3 in T lymphocytes at the level of elongation by inducing eEF2-phosphorylation and thereby inhibiting its activity (Gutzkow et al, 2003). Moreover, it is known that cyclin D3 is degraded via proteasome when cells are subjected to tumor necrosis factor (Hu et al, 2002) or under hyposmotic stress (Tao et al, 2002). Our results indicating that cyclin D3 degradation might be induced in cells under different conditions of hyperosmotic stress (NaCl, sodium arsenite or cadmium sulfate) in a proteasome-depending manner are in agreement with these reports.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the factors involved in cyclin D3 transcription are largely unknown, recent reports indicate that cyclin D3 levels might be regulated by degradation via proteasome after hyposmotic stress (Tao et al, 2002) or in cells treated with tumor necrosis factor-a (Hu et al, 2002). It has also been shown that the formation of ternary complexes cyclin D3-cdk4 and p21 Cip1 or p27 Kip1 stabilizes the D1 and D3 cyclins (Bagui et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from enterotoxins, pore-forming toxins such as Staphylococcus aureus -toxin [35] and PorB of Neisseria gonorrhoeae [36] also induce intrinsic apoptosis. HRT-18 cells were chosen as they are extensively used in apoptosis studies [37,38]. IEC-18 cells, on the other hand, were chosen since in vivo studies conducted on STb are often undertaken using a rat model as an alternative to the pig.…”
Section: Discussionmentioning
confidence: 99%